PENGARUH KUALITAS PELAYANAN BERBASIS CHATBOT TERHADAP KEPUASAN MAHASISWA SISTEM INFORMASI ARS UNIVERSITY - Hussain, Richard Thariq; Handayani, Rissa Nurfitriana; Cahyana, Mochammad Anwar; Rizaldy, Tirto (Universitas Majalengka, 2024)
The quality of chatbot-based services has become a significant focus among higher education institutions in their efforts to enhance student satisfaction. The use of chatbot technology in academic services provides ease and speed in accessing information, thus improving service efficiency. This study aims to analyze the impact of chatbot service quality on student satisfaction within the Information Systems program at ARS University. A quantitative research method with a linear regression approach was used to examine the causal relationship between the independent variable (chatbot service quality) and the dependent variable (student satisfaction). Data were collected through online surveys distributed to a randomly selected sample of Information Systems students who utilized the chatbot service. The findings indicate a positive and significant effect of chatbot service quality on student satisfaction. The regression analysis revealed that an increase in chatbot service quality leads to a corresponding increase in student satisfaction. These results suggest that for universities to improve student satisfaction, continuous enhancement of chatbot services is essential. Effective chatbot services that are responsive, informative, and easy to use can significantly enhance the overall student experience by providing timely and accurate responses to student inquiries. This research underscores the importance of integrating well-designed chatbot services in academic settings to boost both the quality of service and student satisfaction.